2002
DOI: 10.1006/jfan.2002.3928
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Inner Multipliers on Spaces with Complete Nevanlinna Pick Kernels

Abstract: 2 ðDÞ. They show that if k is a complete NP kernel and if D is a separable Hilbert space, then for any scalar multiplier invariant subspace M of Hðk; DÞ there exists an auxiliary Hilbert space E and a multiplication operator F : Hðk; EÞ ! Hðk; DÞ such that F is a partial isometry and M ¼ FHðk; EÞ. Such multiplication operators are called inner multiplication operators and they satisfy FF * ¼ the orthogonal projection onto M. In this paper, we shall show that for many interesting complete NP kernels the analogy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 13 publications
(31 reference statements)
2
57
0
Order By: Relevance
“…Because of its connection to various topics in operator theory, e.g. the von Neumann inequality for commuting row contractions, H 2 n has been the subject of intense recent studies [1]- [7], [9], [10], [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its connection to various topics in operator theory, e.g. the von Neumann inequality for commuting row contractions, H 2 n has been the subject of intense recent studies [1]- [7], [9], [10], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the recent results related to multipliers, we would like to mention the following developments. Interpolation problems for multipliers and model theory related to the Drury-Arveson space have been intensely studied over the past decade or so [4,5,10,12]. Recently, Arcozzi, Rochberg and Sawyer gave a characterization of the multipliers in terms of Carleson measures for H 2 n [1].…”
Section: Introductionmentioning
confidence: 99%
“…See [4] for details. Greene, Richter, and Sundberg [7] have shown that when Ω = B d (the unit ball of C d ) and the kernel k satisfies some mild additional assumptions, the vector-valued multiplier Φ(ζ) is a coisometry almost everywhere on the boundary of B d , strengthening the analogy with the usual Beurling theorem. In the case of the Szegő kernel, the function b is b(z, w) = zw.…”
Section: Now Consider ω = D (The Open Unit Disk) and Let S Be The Szementioning
confidence: 83%
“…This completes the proof. In [GRSu02], Green, Richter and Sundberg prove that for almost every ζ ∈ ∂B n the nontangential limit Θ(ζ) of the inner multiplier Θ is a partial isometry. Moreover, the rank of Θ(ζ) is equal to a constant almost everywhere.…”
Section: By Corollary 52 There Exists An Isometric Module Mapmentioning
confidence: 99%